HISTORY AS AN IDEOLOGY: NEW ORDER IN A HISTORY SCHOOL TEXTBOOK - Mulyana , Agus; Komariah, Aan (International Journal of Psychosocial Rehabilitation, 2020)
During Indonesia’s New Order period, history school textbooks received special attention from the Suharto’s governance. The history of instructional materials must be in accordance with the curriculum designed by the government. These instructional materials, as one would expect, inevitably contained political agendas of the ruling government. This paper reported a critical discourse analysis on the political ideology contained in the historical narratives portrayed by the school textbook during the New Order regime.